2012
DOI: 10.1007/s11046-012-9599-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA-hsp65 Vaccine as Therapeutic Strategy to Treat Experimental Chromoblastomycosis Caused by Fonsecaea Pedrosoi

Abstract: Chromoblastomycosis (CBM) is a chronic subcutaneous mycosis, caused by several dimorphic, pigmented dematiaceous fungi. Patients with the disease are still considered a therapeutic challenge, mainly due to its recalcitrant nature. There is no "gold standard" treatment for this neglected mycosis, but rather there are several treatment options. Chemotherapy alternatives include 5-flucytosine, itraconazole, terbinafine, fluconazole, thiabendazole, ketoconazole and amphotericin B, although the healing of severe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
10
0
4
Order By: Relevance
“…Footpad infection with F . pedrosoi propagules is already known to establish experimental CBM with skin lesions and histopathological features similar to that found in humans [18,23,42,43] and it is used here as a positive control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Footpad infection with F . pedrosoi propagules is already known to establish experimental CBM with skin lesions and histopathological features similar to that found in humans [18,23,42,43] and it is used here as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…pedrosoi (ATCC 46428) was cultivated in Sabouraud Dextrose Agar medium (SDA, Himedia) supplemented with 100 mg.l -1 chloramphenicol at 37°C, as described previously [23]. Fungal virulence and strain adaptation to an animal host was acquired by sequentially inoculating F .…”
Section: Methodsmentioning
confidence: 99%
“…After prolonged use, a lichenoid infiltrate may develop as a reflection of increased local immunity. Siqueira et al (315) developed an experimental DNA-hsp65 vaccine to stimulate adaptive immunity, with promising results not only for therapy but also for CBM prophylaxis in animal models. This drug has been combined with itraconazole, with an important improvement of experimental cutaneous lesions (315).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Our group has previously reported the immunostimulatory properties of the Mycobacterium leprae 65-kDa heat-shock protein (DNA-Hsp65), which is protective against M. tuberculosis [17-19] and effective as an immunomodulatory agent in several diseases, such as leishmaniasis [20], paracoccidioidomycosis [21], chromoblastomycosis [22], diabetes [23], arthritis [24], allergy [25] and phase I cancer trials [26,27]. Our group also reported that in a model of S. mansoni egg-induced fibrosis, the administration of DNA-Hsp65 reduced fibrotic processes during granuloma formation and led to a decrease in collagen deposition at the injury site [28].…”
Section: Introductionmentioning
confidence: 99%